Carl Sandburg papers - Sandburg, Carl, 1878-1967.
Correspondence with Edward R. Murrow, Sophocles Papas, Robert Penn Warren, and others; holograph poems including poem entitled, Fog (undated); essays on Walt Whitman and other subjects; speeches concerning Abraham Lincoln; and other papers relating chiefly to Sandburg's career as a poet and biographer of Lincoln.
In part, positive photocopies and typewritten transcripts.
Author and poet.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Lincoln, Abraham, -- 1809-1865.; Murrow, Edward R. -- Correspondence; Papas, Sophocles, -- 1893-1986 -- Correspondence; Warren, Robert Penn, -- 1905-1989 -- Correspondence; Whitman, Walt, -- 1819-1892.; American literature; American poetry; Authors; Poets